Case Report: A Case of Infant Bronchial Dieulafoy's Disease and Article Review - Chen, Yang; Mao, Yiting; Cheng, Xingfeng; Xiong, Ruihua; Lan, Ying; Chen, Feng; Zhang, Furong; Liu, Jun; Wu, Yanting (Frontiers in Pediatrics, 2021)
Abstract: Background: Bronchial Dieulafoy’s Disease (BDD), characterized by constant diameter arterial malformation, is a rare disease especially among younger children. The pathogenesis as well as the clinical features of pediatric patients are insufficient. Misdiagnosis and operations of biopsy may lead to potential massive hemorrhage which endangered patient’s life. The aim of this study is to conclude the clinical features of pediatric patients of BDD with an age up to 14 years old. Case presentation: We here present a case of a 9-months old boy who was diagnosed as BDD, with massive hemoptysis. The boy was cured by the treatment of embolization of bronchial artery and was in good health in a year’s follow up. Besides, we researched the key word as “Bronchial Dieulafoy’s Disease (BDD)” on the databases of PubMed, Google Scholar, and Web of Science and found another two cases of pediatric BDD. Conclusion: It is still insufficient to draw out the conclusion of the origin of the disease. Bronchial angiography and endobronchial ultrasonography are considered as promising methods to diagnose Dieulafoy’s disease of bronchus. Bronchoscopy biopsy shall not be deployed due to the high risk of fatal hemorrhage. Explicit clinical case reports of BDD are needed to enhance the understanding of this rare disease.